Diabetic Macular Edema Treatment with Bevacizumab Does Not Depend on the Retinal Nonperfusion Presence. (27th February 2021) - Sędziak-Marcinek, Bogumiła; Teper, Sławomir; Chełmecka, Elżbieta; Wylęgała, Adam; Marcinek, Mateusz; Bas, Mateusz; Wylęgała, Edward
Abstract : This study evaluated the relationship between the retinal nonperfusion area (NPA) presence and the effectiveness of bevacizumab treatment (IVB) in patients with diabetic macular edema (DME). It also tested the prognostic usefulness of ultra-wide-field fluorescein angiography (UWFFA) and OptosAdvance software for diabetic retinopathy monitoring. Eighty-nine patients with DME with a macular central   subfield   thickness   CST ≥ 250   μ m, with (N = 49 eyes) and without (N = 49 eyes) retinal NPA, underwent nine bevacizumab injections over 12 months. NPA distribution, leakage area distribution, microaneurysm (MA) count, macular CST, diabetic retinopathy severity, and best-corrected visual acuity (BCVA) were assessed. The results show that bevacizumab reduced the macular CST from 420 to 280  μ m (p < 0.001 ) and improved BCVA (p < 0.001 ) by about 10 ETDRS letters in both groups of patients. Additionally, the therapy reduced total retinal NPA from 29 (14-36) mm 2 to 12 (4-18) mm 2 (Me (Q1-Q3); p < 0.001 ) in patients with diagnosed nonperfusion. The effect of the therapy measured with vascular leakage, MA count, BCVArelative, and CSTrelative strongly depended on the zone of the retina and the NPA distribution. We conclude that the bevacizumab treatment had a positive effect on DME and BCVA in both study groups and on the size of retinal NPA in patients with retinal nonperfusion.